Precision dosing of vancomycin: in defence of AUC-guided therapy in children. (7th June 2021) - Murphy, Mark E; Tang Girdwood, Sonya; Goldman, Jennifer L; Scheetz, Marc H; Downes, Kevin J
Abstract: In 2020, new vancomycin guidelines were released, recommending the transition from trough-based to AUC24 monitoring for adult and paediatric patients. Given the resources required to achieve this transition, there has been debate about the costs and benefits of AUC24 -based monitoring. A recent narrative review of vancomycin therapeutic drug monitoring in paediatrics claims to have uncovered the methodological weaknesses of the data that informed the guidelines and advises against premature adoption of AUC24 -guided monitoring. In this article, we present supporting arguments for AUC24 -guided monitoring in children, which include that: (i) troughs alone are inadequate surrogates for AUC24 ; (ii) vancomycin-associated nephrotoxicity has significant consequences that warrant optimization of dosing; (iii) a substantial portion of children receiving vancomycin are at high risk for poor outcomes and deserve targeted monitoring; and (iv) limited efficacy data in support of AUC24 is not a justification to revert to a less supported monitoring approach.